2023
DOI: 10.31234/osf.io/egp82
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for mood instability in patients with bipolar disorder: Applying multilevel hidden Markov modelling to intensive longitudinal ecological momentary assessment data

Abstract: Background. Bipolar disorder (BD) is a chronic psychiatric condition characterized by large shifts in mood, energy, and cognitive functioning. Recently, the conceptualization of BD has shifted from alternating discrete episodes to a chronic cyclical mood instability model. Recog-nizing and quantifying this mood instability may improve care and calls for high-frequency measures coupled with advanced statistical models. Methods. To uncover empirically derived mood states, a multilevel hidden Markov model (HMM) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Importantly, the total sample size (Number of Participants × Number of Assessments) is comparable with previous studies that explore switches in latent mood states of patients with BD (e.g., Cochran et al, 2016;Prisciandaro et al, 2019;Yee et al, 2021). Indeed, previous research in MHMMs has demonstrated that parameters are accurately estimated with smaller samples when the number of assessments is sufficiently large (McClintock, 2021;Mildiner Moraga & Aarts, 2024). However, clinically, the sample was small and quite heterogeneous (e.g., both BD Type I and II, males and females, with different comorbidities and medication types), and participants were selected based on a clinical history of frequent manic or depressive episodes.…”
Section: Discussionsupporting
confidence: 56%
“…Importantly, the total sample size (Number of Participants × Number of Assessments) is comparable with previous studies that explore switches in latent mood states of patients with BD (e.g., Cochran et al, 2016;Prisciandaro et al, 2019;Yee et al, 2021). Indeed, previous research in MHMMs has demonstrated that parameters are accurately estimated with smaller samples when the number of assessments is sufficiently large (McClintock, 2021;Mildiner Moraga & Aarts, 2024). However, clinically, the sample was small and quite heterogeneous (e.g., both BD Type I and II, males and females, with different comorbidities and medication types), and participants were selected based on a clinical history of frequent manic or depressive episodes.…”
Section: Discussionsupporting
confidence: 56%
“…However, many other models or descriptive statistics can be used to capture relevant features of the time series. In this context, an interesting class of models that has not been widely used in the emotion dynamics literature are Hidden Markov Models (HMMs), which model time series as generated by unobserved latent time-varying states (for a recent application in the context of emotion time series, see Mildiner Moraga et al, 2023). The number and nature of latent states found by fitting HMMs to empirical data could potentially be used to inform the situation part of our generative model, or to fine-tune the modeling of emotion variables as consisting of distinct states.…”
Section: Discussionmentioning
confidence: 99%